How Do StudentsImplement E-Learning During the Covid-19 Pandemic? - Faisal Hafidh Yanuar Ramadhan; Herwin Herwin (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to find out how the implementation of E-Learning on students during the Covid-19 pandemic. The importance of this research is to find out how students carry out E-Learning well during the pandemic, there will be suggestions for other students in implementing E-Learning in order to get good results. This research is a phenomenological qualitative research. The subjects of this study were 19 third semester students of class 3B Master of Basic Education, Yogyakarta State University. Data collection techniques are interviews, questionnaires and documentation. Meanwhile, data analysis was carried out through data condensation, data presentation and verification. The results of this study indicate that students state that E-Learning is a new challenge for students during the Covid-19 pandemic. In order to overcome these challenges, students have several factors that influence the implementation of E-Learning in the Covid-19 pandemic, namely 1. Students are required to create a mindset to continue and want to learn; 2. Students manage time well between studying and getting enough rest; 3. Collaboration with peers to help each other and learn; 4. The level of student discipline in doing assignments and; 5. The sincerity of students in carrying out lectures. These factors affect student learning outcomes in achieving an average GPA of 3.79.